ANALISIS KINERJA KEUANGAN PERBANKAN SEBELUM DAN SESUDAH PENERAPAN BRANCHLESS BANKING DI INDONESIA - Dizzahara, Izhellia Oktatubela; Sakti, Rachmad Kresna (Contemporary Studies in Economic, Finance and Banking, 2022)
To improve financial inclusion, the government, through the Financial Services Authority (OJK), organized the Branchless Banking (Laku Pandai) program which aims to flatten the provision of formal financial institutions access. In this program, banks can expand their reach without constructing physical offices through collaboration with bank agents as financial intermediaries. This study aims to analyze the banking financial performance using CAMEL method on each Conventional Commercial Banks before and after the implementation of Branchless Banking in year of 2010-2019. This study uses a quantitative approach with the comparative research type and using non-parametric statistical test equipment (Wilcoxon signed-rank test) on its hypothesis test. Sample determination uses a purposive sampling technique resulting in the usage of 7 Conventional Commercial Banks (BRI, Mandiri, BTPN, BCA, BTN, BNI, and BPD Kaltim) as samples in this study. The results showed that in the CAR ratio, there were 7 banks that experienced significant differences. In the NPL ratio, there were 4 banks with significant differences. There were 3 banks that experience significant differences in NPM ratio. While, there were 6 banks with significant differences in its ROA. Last, the LDR ratio showed 6 banks that experience Branchless Banking in Indonesia.